The Effect of Financial Resources on Fertility: Evidence from Administrative Data on Lottery Winners - Tsai, Yung-Yu; Han, Hsing-Wen; Lo, Kuang-Ta; Yang, Tzu-Ting (Journal of Labor Economics, 2026)
This paper utilizes wealth shocks from winning lottery prizes to examine the causal effect of financial resources on fertility. We employ extensive panels of administrative data encompassing over 0.4 million lottery winners in Taiwan and implement a triple-differences design. Our analyses reveal that a substantial lottery win can significantly increase fertility, the implied wealth elasticity of which is around 0.06. Moreover, the primary channel through which fertility increases is by prompting first births among previously childless individuals. Finally, our analysis reveals that approximately 25% of the total fertility effect stems from increased marriage rates following a lottery win.